Fracture Resistance of Equine Cheek Teeth With and Without Occlusal Fissures: A Standardized ex vivo Model - Pollaris, Elke; Broeckx, Bart J. G.; Rajasekharan, Sivaprakash; Cauwels, Rita; Vlaminck, Lieven (Frontiers in Veterinary Science, 2021)
Background: Ex vivo fracture models are frequently used in human dentistry to provide insights in the fracture mechanisms of teeth. Equine cheek teeth fractures are an important dental pathology, but there has been no research performed to examine the fracture resistance ex vivo. Objective: To evaluate the fracture resistance of equine cheek teeth and identify anatomical predictors that might influence fracture resistance in healthy teeth. It was further evaluated if the presence of a fissure caused a decrease in fracture resistance. Study design: Ex vivo experimental design. Methods: Individual cheek teeth were subjected to a compression load in a universal testing machine until fracture occurred. Testing was performed in 2 study groups. A first group of healthy cheek teeth was tested to examine anatomical predictors on fracture resistance. A second group comprised cheek teeth with occlusal fissures and an equal number of age- and size-matched fissure-free teeth as controls. The effect of possible predictors on fracture resistance was investigated by regression analysis. Results: In the first group, fracture resistance was significantly influenced by the location on the tooth where testing was performed in both maxillary (p < 0.001) and mandibular teeth (p < 0.001). Additional significantly associated factors were Triadan number in mandibular (p = 0.009) and the mesiodistal length of the occlusal surface of maxillary teeth (p = 0.01). Experimentally induced crown fractures that extended below the simulated bone level were more frequently associated with pulp horn exposure (p < 0.001). In the second group, significant lower fracture loads were recorded in teeth with fissures (mandibular p = 0.006; maxillary p <0.001), compared to fissure-free teeth. Main limitations: This ex vivo model does not imitate the in vivo masticatory forces and lacks the shock-absorbing properties of the periodontal ligament. Conclusions: The methodology used in this study provides an ex vivo experimental set-up to test fracture resistance of equine cheek teeth enabling evidence-based research to examine the potentially weakening effects of tooth pathology and its treatments. Crown resistance to fracture differed along the occlusal surface of healthy equine cheek teeth, and the presence of fissures further decreased fracture resistance.